Experimental Validation of Mander's Model for Low Strength Confined Concrete under Axial Compression - Ali, M. (Institute of Electrical and Electronics Engineers Inc., 2020)
Reinforced Concrete is one of the largest used building materials in the world. Previous research shows the performance of standard and high strength concrete in axial compression and ductility. In the past decade, extensive research has been conducted on the stress-strain behavior of confined high strength concrete under axial compression. But only a few studies have been concerned with the experimental and analytical of low strength confined concrete under axial compression. In this research, an experimental and analytical approach to reinforced concrete confinement behavior of low strength under axial compression was carried out. A comparison of experimental results with Manders model to validate the analytical models for low strength concrete. A total of nine square column specimens with a cross-section of 9Ã9 inch and 18-inch length having six longitudinal and transverse reinforced and three without reinforced -column specimens of different ties spacing for 28 days and eighteen cylinders without reinforcement having nine from the localized construction area and nine were designed with different water/cement ratio ranging from 0.5 to 0.7 with a diameter of 6 inches and 12-inch height for 7 days were used for axial monotonic loading low strength concrete. The longitudinal reinforcement consists of 4#4 bars and the transverse reinforcement consists of #3 bar hoops. Each set of three columns were confined with 5 to 7-inch c/c ties spacing and carried out. Experimental results show that the capacity of column specimen and ultimate compression strain of low strength concrete significantly increased by increasing the volumetric transverse steel ratio. The maximum compressive strength for the low strength concrete without reinforcement was achieved on a 0.6 w/c ratio as compare to others. The effect of transverse steel confinement in low concrete strength is greater and compared with Mander's model. There was a slight variation in the experimental results and Mander's analytical model validation for low strength concrete. Â© 2020 IEEE.